Productivity Analysis Using Objective Matrix (OMAX) Method: Case Study On The Production Departement of Sari Roti PT Nippon Indosari Corpindo, Tbk Pasuruan - Hamidah, Nurul Hazmi; Deoranto, Panji; Astuti, Retno (Jurnal Teknologi Pertanian, 2013)
The purpose of this study was to determine the level of partial and total productivity on the production department of Sari Roti PT Nippon Indosari Corpindo, Tbk Pasuruan with productivity measurement was carried out in January to December 2012. The result of this research can be used as the benchmark productivity and basis of planning for increasing productivity in future periods. Objective Matrix (OMAX) methods was used for analyzing the data. Criteria of productivity used in this study were the use of raw material, man hour, fuel, and electrical energy. The results showed that the highest score of productivity was on the use of man hour which was achieved in October at level 9. The criteria for the use of raw materials, fuel, and electrical energy reached the lowest score of 0 on November and December. The highest value of total productivity index level achieved during the measurement period was 84.69% in October and the lowest value was -95.18% in November. Unsuitable raw material received, defective parts, discomfort working environment, lack of discipline, lack of motivation, and too tired workers were factors that lead to low productivity in the production department of Sari Roti PT Nippon Indosari Corpindo, Tbk Pasuruan.Keywords: Objective matrix (OMAX), bakery industry, productivity